Granting Permission for Registering Interfaith Marriage in Indonesia; The Marriage Law and The Human Rights Law Perspective - Karim, Ahmad Busyrol; Ramsay, Sahur (UIN Sunan Kalijaga Yogyakarta, 2024)
Interfaith marriage always controversial in Indonesia. The granting of permission to register interfaith marriages has been rampant in the District Court before the existence of Supreme Court Circular Letter No. 2 of 2023 concerning the prohibition of registering interfaith marriages. The granting of permission to register interfaith marriages is very controversial because it is not clearly regulated in the marriage law. Surabaya District Court with Number: 916/Pdt.P/2022/PN.Sby has given permission for registering interfaith marriages. This research aims to find out the legal considerations of the judge in granting permission for registering interfaith marriages, and to analyze the decision in terms of the Marriage Law and the Human Rights Law. This study is a library study with a normative juridical approach. It uses the legality theory and the universality and relativity theory of human rights. This study concludes that the judge has considered the human rights of the petitioners to grant the registration of marriage between different religions. In terms of the Marriage Law, the legal considerations used by the judge are not quite right, because the article explains that marriage is prohibited if it is prohibited by religion, and all religion in Indonesia prohibit interfaith marriage. In terms of the Human Rights Law, it is explained that a marriage is valid if it is in accordance with the provisions of the applicable laws and regulations, so that the legalization of marriage should refer to the Marriage Law.